Rancang Bangun Aplikasi Dicom Viewer Pada Android Yang Terintegrasi Dengan PACS - Yogiyanto, Hendri; Sutanto, Teguh; Romeo, Romeo (Jurnal JSIKA, 2012)
Medical imaging becomes a general need to diagnose and do acute illness surgery nowadays. However, medical imaging is not as that easy, it takes training and experience, so it is not surprising that the radiologist must have a greater ability in conducting and interpreting imaging procedures than any other clinical personnel. Therefore, the availability of radiologists to afford the needs of the hospital in giving radiology interpretation services becomes important and becomes the main attention at the moment, especially for the Emergency Department in providing emergency medical services at night and holidays. Radiologist availability problems can be overcome if there is a system that allows radiologists can still perform medical analysis without having to come directly to the medical center location. Teleradiology applications can give solution to this problem. With this teleradiologi module, hospital that has used MedInfo Storage Server can manage the problem of lack of availability of radiologists, especially in the evenings and holidays. Teleradiology module integration with the PACS server can answer the needs of medical service center to support diagnosing digital medical image data. Keywords: DICOM, PACS, teleradiology